CIRCULAR ECONOMY BUSINESS MODELS IMPLEMENTATION IN THE GREEN ENERGY DEVELOPMENT IN UKRAINE - Марта Злотнік; Олександр Маслак; Андрій Кузь (Економіка та суспільство)
Іs devoted to exploring the possibilities of adopting circular business models within Ukraine's green energy sector. This approach is intended to enhance resource efficiency, decrease waste, lessen environmental effects, and contribute to economic recovery following the war. The following business models of the circular economy were considered: closed-loop model, product-as-a-service model, product life cycle extension model, sharing model, and resource recycling and reuse model. A SWOT analysis was carried out to identify the strengths, weaknesses, opportunities and threats associated with the implementation of circular models in the country's renewable energy sector. The results of the study show that effective adaptation of circular economy models in the green energy sector in Ukraine requires comprehensive support from the state, attraction of international investments, and development of new mechanisms to stimulate environmental responsibility in the business environment. The proposed strategies and measures can ensure Ukraine's sustainable development and facilitate its integration into the international renewable energy market with high environmental standards.